UPAYA MEREDUKSI PERILAKU PROKRASTINASI AKADEMIK MELALUI KONSELING KELOMPOK DENGAN TEKNIK SELF MANAGEMENT (Studi Kasus di Kelas XI SMA Negeri 2 Palu) - Abdullah, Abdullah; Thalib, Mansyur; Munifah, Munifah (Tadulako University, 2016)
This researh aims to reduce academic procrastination behavior of the student using group sounseling with self management technique. This was an action researh of guidance and counseling using Kemmis and Mc Taggart model. The researh was carried out in two cycle with four stage in each cycle, namely: planning, action, observation, and reflection. Subjects of the research were 6 student who have academic procrastination problem. The action conducted was group counseling with self management technique. Data collection method was observation and interview. The research results reveal that after conducting cycle I, the behavior of procrastination of the student decreased to 19.62%. While in cycle II it decreased to 13.59%. It indicates that self management technique in cycle II is improved based of reflection outcomes in cycle I. Therefore, it can be concluded that academic procrastination behavior of the student can be decreased using group counseling with self management technique.